2014
DOI: 10.1177/0009922814538492
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Fontanelle Closure and Size in Full-Term Children Based on Head Computed Tomography

Abstract: This study provides reference charts detailing AFC frequency and AF SA as a function of age. Wide variability of AFC timing and AF size among healthy infants suggest that early or delayed AFC may represent normal variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 16 publications
5
44
2
2
Order By: Relevance
“…For example, auricular height (eam‐v) only showed significant changes between the ages of 0–4 years, meaning growth of this dimension likely finishes at around 4 years. This finding parallels the closing of cranial fontanels, which generally occurs during early postnatal life (birth to 4 years) , and supports other studies that suggest neural growth corresponds with cranial braincase growth . Other dimensions measured from the same point (eam) to superior regions of the facial skeleton (n and ns) showed similar patterns of growth to auricular height, with faster growth in childhood (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…For example, auricular height (eam‐v) only showed significant changes between the ages of 0–4 years, meaning growth of this dimension likely finishes at around 4 years. This finding parallels the closing of cranial fontanels, which generally occurs during early postnatal life (birth to 4 years) , and supports other studies that suggest neural growth corresponds with cranial braincase growth . Other dimensions measured from the same point (eam) to superior regions of the facial skeleton (n and ns) showed similar patterns of growth to auricular height, with faster growth in childhood (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the earliest recorded clinical fusion in the Māori/Pasifika group occurred at 6 months, and this increased to 30% by 9 months. This rate was significantly higher than several previously recorded populations, including the Indian population, which showed 4% fusion; American 7–14%; Iranian 11%; and Swiss 17% . The populations most consistent with the Māori/Pasifika rates were African populations, with rates of 35% in Nigeria and 40% in Ethiopia at 9 months .…”
Section: Discussioncontrasting
confidence: 58%
“…Although Ant on (1997) favored an age from four to six years, we consider a younger age likely for several reasons. First and foremost is the specimen's open anterior fontanelle, which a recent CT-based study (Pindrik et al, 2014) found to be fully closed by 2.5 years in 90% of 459 healthy humans, though fusion frequency exceeded 50% by 16 months. Second, Coqueugniot et al (2004) found the highest likelihood of observing humans with anterior fontanelle and subarcuate fossa closure comparable to Mojokerto between the ages of 0.5e1.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, comparison with human and chimpanzee developmental series have suggested an age at death between early infancy and up to six years for Mojokerto, and the implications for brain growth in H. erectus depend entirely on its age. There is good reason to believe the individual died younger than two years of age based on recent assessments of metopic suture (Weinzweig et al, 2003;Bajwa et al, 2013) and anterior fontanelle closure in humans (Pindrik et al, 2014), but here we consider the full range of likely age estimates (up to six years) to highlight the importance of this uncertainty for interpreting brain growth in this species.…”
Section: Introductionmentioning
confidence: 99%